DEVELOPMENT OF A STRATEGIC PLANNING MODEL BASED ON DIGITAL TECHNOLOGY TO IMPROVE THE QUALITY OF EDUCATION - Sariakin, Sariakin; Rahmattullah, Rahmattullah (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
This research aims to develop a strategic planning model based on digital technology to improve the quality of education. The research was conducted against the background of the need for educational transformation through digital technology innovation in order to improve the quality of learning and school management. The research method uses a research and development approach with stages of needs analysis, model design, expert validation, testing and implementation. Data collection instruments include interviews, observation and documentation. The research results show that the strategic planning model based on digital technology that was developed has proven to be effective in improving the quality of education, which is characterized by improving teacher performance, learning quality and school administrative management. This model includes digital technology integration strategies, developing digital competency for educators, and technology-based management systems. The use of digital technology in the educational planning process brings a fundamental transformation to the learning system. Through technology integration, processes become more efficient, organized and based on accurate data. Digital technology enables faster, more transparent and more targeted decision making, and encourages constructive collaboration between teachers, students and parents. This approach does not just improve administrative quality, but also creates a dynamic, responsive and innovation-based educational ecosystem. The research recommendation is the need for continued support from stakeholders in implementing digital technology-based strategic planning models in schools.